Designing an Efficient Management System Modeling of Convergence Factors Exemplified by the Case of Japanese Businesses in Thailand - Raoprasert, Tanachart; Islam, Sardar M. N.; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD, 2010)
This book makes a significant and valuable contribution to the literature in the fields of organisational behaviour and design, performance analysis and structural equation modelling. The subject of this book is the development of an efficient and effective management system in the globalised world in order to improve overall organizational performance to achieve good corporate governance by reducing agency costs in a cross-cultural environment. Based on an empirical case study of Japanese management practices in Thailand, it examines factors that help to adapt management practices to the work culture of the host country and motivate local employees to adapt and implement unfamiliar management practices. The book provides a new methodological approach by applying structural equation modeling to psychosocial and motivational constructs of organizational performance, and thus presents an innovative behavioral framework of organizations in a contemporary cross-cultural setting.
Literature Review -- Theoretical Framework -- Methodology, Research Process, and Computer Programs -- Preliminary Data Analysis and Results: Descriptive Statistics and Reliability Tests -- Structural Equation Modeling: Results and Analysis -- Discussion and Implications -- Summary, Findings, and Conclusion -- Appendices.
Keywords: Economics; Business planning; Personnel management; Economics/Management Science; Organization/Planning.; Personnel Management